Novel 3D conformal technique for treatment of choroidal melanoma with external beam photon radiotherapy. Issue 2 (7th January 2013) - Phillips, Claire; Pope, Kathy; Hornby, Colin; Chesson, Brent; Cramb, Jim; Bressel, Mathias
Abstract Introduction To report a 3D conformal radiotherapy (3D‐CRT) technique that utilises a specific eye immobilisation and treatment set‐up method as an alternative to stereotactic radiotherapy (SRT), for treatment of juxtapapillary choroidal melanoma (CM) and report early treatment outcomes of this technique. Methods A contact lens and rod system was designed to provide eye immobilisation and a treatment reference point for 3D‐CRT. The technique is described in detail in the body of the paper. A retrospective chart review was conducted to report freedom from local progression (FFLP) and radiation toxicity in a cohort of patients treated with a dose of 50 Gy in five fractions. Results Eleven eligible patients with juxtapapillary CM were treated between 2003 and 2009. The median follow‐up was 3.2 years (range 1.2–5.3). The FFLP was 100% (95% confidence interval 71.5–100). The reproducibility of the set‐up and eye immobilisation for fractionation was excellent. The mean dose to the planning target volume was 51.4 Gy (interquartilic range 51.0–51.9). Normal tissue dose constraints were achieved; however, the quality of the 3D‐CRT plan was variable. The highest acute radiation toxicity score was Common Toxicity Criteria version 3 grade 1. Vision outcomes were poor. Conclusion In this small series, a novel non‐stereotactic technique was found to be an accurate method for the treatment of CM with a high rate of freedom from tumour progression, in keeping with the SRT series. The quality of the conformal plan was variable. Investigation of the optimal dose‐fractionation schedule to minimise late radiation toxicity without compromise of tumour control is the focus of ongoing clinical research at our centre.